J. Bassas, Jacques Rancière: Ensayar la igualdad, Madrid, Gedisa, 2019, 142 pp. - González Fonseca, Diana Mitzi (Res Publica. Revista de Historia de las Ideas Políticas, 2021)
Reseña de la obra de Bassas, Jacques Rancière: Ensayar la igualdad, Madrid, Gedisa, 2019, 142 pp.